The Significance of Death in Dylan Thomas’s Poetry (Journal of the College of Basic Education, 2022)
This study is about the significance of the concept of death in Dylan Thomas’s poetry. The poet presents his views about the death in a way that easily touch the reader, but there are serious flows about his concept from the Islamic perspective in his poem “Do not go gentle into that good night”. The poet asks his dying father to fight against death by doing good and strong actions to achieve greatness after his death. The poet has a point, and what he asks for is significant, but he asks that at the waste time. The study approved that through the Islamic perspective, the man cannot do good deeds as he is approaching, and it is not important for the man to achieve greatness after his death as much as what he is going to face in the grave and the Hereafter. The study also approved that the time of doing or even believing is over when death comes in Islam. The researcher recommends that the learner as much as the teacher should be aware of the fact that death is a global concept with various views among religious and cultures, but all of them are worthless compared to Islam. And since the concept presented through literature, specially foreign literature, is very important and matters all people, then it should be discussed through the Islamic perspective because Islam is not only a religion, but rather it is a life method that should be adopted in every single educational situation.